The response of companies to information-based environmental policies - Domenico Siniscalco; Stefania Borghini; Marcella Fantini; Federica Ranghieri (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper investigates the companies' behavioural response to information-based environmental policies. We perform a panel analysis for 39 big companies in 16 countries, in 3 polluting industries (oil & gas, chemicals, power generation) over a 5- year period (1993-1997) to check whether environmental policies (command and control and energy taxation) and the adoption of information-based environmental strategies affect the companies' economic and environmental performance. The results confirm the positive role of self-regulated environmental audits and compensation programmes on corporate environmental performance.
Keywords: D2; J3; L2; M2; 330; Environmental policy; corporate environmental management; corporate compensation programmes; information-based environmental policies; Umweltpolitik; Umweltmanagement; Industriestaaten